Application of personalised medicine to solid tumours: opportunities and challenges (Swiss Medical Weekly, 2012)
Personalised medicine is an emerging model that will revolutionise our current healthcare system. In the last decade, several genomic aberrations were discovered that are now used as predictive markers for treatment with targeted therapeutics. The technological advances in the last few years, such as the development of high resolution DNA microarrays or second generation sequencers, have led to a dramatic increase in the number of ongoing genomic profiling studies. These studies, in turn, are leading to an enormous number of detected genomic aberrations whose biological interpretation is still pending. This review will provide an overview on the current state of personalised medicine in cancer. Discussion of the use and development of the various technologies will help us to understand the opportunities and challenges that arise when novel technologies are implemented.